PENGARUH MIKORIZA ARBUSKULA DAN INANG Portulaca sp. TERHADAP AKLIMATISASI PLANTLET CENDANA (Santalum album L.) - Toni Herawan; Asri Insiana Putri (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
Cendana (Santalum album Linn.) produces high-value aromatic timbers that are needed in various industries. Cendana is proclaimed by IUCN including critically endangered tree species. Tissue culture for conservation and propagation of cendana is a promising technique to lessen endangered level and increase industrial raw material supply. The main problems of cendana tissue culture are stunted growth and high mortality of plantlet at acclimatization stage. The purpose of this research is to identify the effect of arbuscular mycorrhizal application in acclimatization of cendana tissue cultured plantlets with and without hostplant. A.III.4.14 clones from Genetic Conservation Plot in Gunung Kidul, Yogyakarta were used as rooting plantlet material; Acaulospora sp. and Gigaspora sp. were used as MA isolates, and Portulaca sp. was used as hostplant. Sand and compost were used as media acclimatization in nurseries. Fungicide solution was used for sterilizing plantlets. Cendana plantlets were planted together with the host and MA added according to the treatment. Incubation was carried out in a greenhouse for 16 weeks. Observation of seedlings height was carried out 4 weeks after the polybag cover opened. The results of this study showed that 5 grams and 7 grams of mycorrhizal treatment on a cendana plantlet planted without Portulaca sp. produced the lower mortality (8%) after 12 weeks incubation. The best average seedling height growth was in 5 grams MA with hostplant (5,17 cm ±1,21) after 16 weeks incubation in green house. The results of this study prove the importance of exogenous mycorrhizal enrichment and hostplant in the acclimatization of cendana tissue culture.